Development of reading comprehension in preschool children based on the narration of modern children's stories - Alvarez, Silvia Juliana; Murillo León, Maritza; Sierra , Edith Johana (Rastros Rostros, 2024)
This article arises from the formative research, carried out in the transitional grade, morning session of the San Cristobal Educational Center, located in the north of the city, in charge of the teacher Rosario Diaz. The central axis of this exercise is referred to the development of reading comprehension in preschool children from the narration of children's stories.